Finite element analysis of glass fibre reinforced thermoplastic composites fore structural automotive components - Wilson, Martin J. (2003)
This thesis describes the investigation and development of damage modelling techniques for woven long glass fibre reinforced polypropylene matrix composites. The objective of the work was to develop and validate predictive models for the intralaminar damage behaviour of these materials, with the aim of applying the results to an industrial demonstrator component.